An Economic and Agronomic Profile of Florida’s Sod Industry in 2003 - John J. Haydu; N. L. Satterthwaite; John L. Cisar (EDIS, 2005)
Information is presented on production, employment, marketing, and product quality and price as a result of a survey of the Florida sod industry for the year 2003, the fourth in a series of surveys since 1992. Total sod production in Florida was estimated to be 92,950 acres. Sixty-four percent of Florida sod acreage was St. Augustinegrass of which more than two-thirds (69%) was Floratam. Bahiagrass comprised 24 percent of sod in production in 2003 and bermudagrass and centipedegrass were at 6 percent and 5 percent, respectively. Nearly three-quarters (73%) of Florida sod production occurred on sandy soils. The majority of sod production was in south Florida. Harvested sod accounted for 68 percent of the sod in production and medium-sized farms harvested the highest percentage of their production acres (82%). The in-field value for all varieties totaled $405 million, while harvested sod was valued at $307 million. Levels of mechanization and employment remained the same over the last three years for the majority of sod farms. The survey showed that 96 percent of all producers expected to maintain or increase current sod production, indicating optimism about future demand. Published by the Institute of Food and Agricultural Sciences University of Florida, Gainesville 32611, April 2005.